Capacity determination of intermodal container frame in resisting housing load - Ong, Zhen Ling (2019)
The shipping container has only been around for the last 50 years. The common functional period of a shipping container in its logistic service can last 10 to 12 years. Used shipping container from logistic service are re-trade in aftermarket for other purposes and usually can sustain for another 10 more years of usage. The increasing numbers of shipping containers which have survived from their serving life span in the logistic service will be considered as ?junk? and causing pollution issue. The concept of recycling shipping container into residential usage can mitigate the issue of the unaffordable demand for rebuilt houses in short period of time for the homelessness due to natural disaster, like flooding in Malaysia which is currently faced by the country government in terms of supplying temporary houses in the short time and budgeted paid to the contractor. However, availability of published and research information on shipping containers utilized as inhabitable purpose is still difficult to obtain as most available publication have not included the topic of the shipping container structural strength and the corresponding structural behavior of shipping containers with other loading scenarios or modification. The purpose of this study is to investigate the capacity of shipping container frame members in resisting residential load and determine the maximum allowable span length of the frame members if stress exceeds the yield strength or deflection exceeds the allowable limit. LUSAS software is used to model the container frame and run using linear analysis. Only edge frame of shipping container is taken into consideration in order to provide more flexibility for builder or architect to modify the shipping container up to their desired standard whereby the corrugated wall or cross members can be removed. The ultimate load combination and deflection limit used is based on BS5400: 2000. The model is built using simple line element with each section properties determined beforehand using section property calculator of LUSAS and assigned accordingly. The results show that intermediate supports are required and necessary to be added so that the maximum member span length is controlled within 2.1 m for top side rails. Additional supports are also required to avoid cantilever structural behaviour within the container.